Temperature Increase Enhances Aedes albopictus Competence to Transmit Dengue Virus - Liu, Zhuanzhuan; Zhang, Zhenhong; Lai, Zetian; Zhou, Tengfei; Jia, Zhirong; Gu, Jinbao; Wu, Kun; Chen, Xiao-Guang (Frontiers in Microbiology, 2017)
Dengue is a mosquito-borne disease that has been an epidemic in China for many years. Aedes albopictus is the dominant Aedes mosquito species and the main vector of dengue in China. Epidemiologically, dengue mainly occurs in Guangdong Province; it does not occur or rarely occurs in other areas of mainland China. This distribution may be associated with climate, mosquito density and other factors in different regions; however, the effect of temperature on the vector competence of Ae. albopictus for dengue viruses remains unclear. In this study, Ae. albopictus was orally infected with dengue virus 2 (DENV-2) and reared at constant temperatures (18°C, 23°C, 28°C and 32°C) and a fluctuating temperature (28-23-18°C). The infection status of the midguts, ovaries and salivary glands of each mosquito was detected by RT-PCR at 0, 5, 10 and 15 days post-infection (dpi). DENV-2 RNA copies from positive tissues were quantified by qRT-PCR. At 18°C, DENV-2 proliferated slowly in the midgut of Ae. albopictus, and the virus could not spread to the salivary glands. At 23°C and 28°C, DENV-2 was detected in the ovaries and salivary glands at 10 dpi. The rates of infection, dissemination, population transmission and DENV-2 copies at 28°C were higher than those at 23°C at any time point. At 32°C, the extrinsic incubation period for DENV-2 in Ae. albopictus was only 5 dpi, and the vector competence was the highest among all the temperatures. Compared with 28°C, at 28-23-18°C, the positive rate and the amount of DENV-2 in the salivary glands were significantly lower. Therefore, temperature is an important factor affecting the vector competence of Ae. albopictus for DENV-2. Within the suitable temperature range, the replication of DENV-2 in Ae. albopictus accelerated, and the extrinsic incubation period was shorter with a higher temperature. Our results provide a guide for vector control and an experimental basis for differences in the spatial distribution of dengue cases.